Navigated liver biopsy using a novel soft tissue navigation system versus CT-guided liver biopsy in a porcine model: a prospective randomized trial - Müller, Sascha A.; Maier-Hein, Lena; Tekbaş, Aysun; Seitel, Alexander; Ramsauer, Stefanie; Radeleff, Boris; Franz, Alfred Michael; Tetzlaff, Ralf; Mehrabi, Arianeb; Wolf, Ivo; Kauczor, Hans-Ulrich; Meinzer, Hans-Peter; et al. (Academic radiology, 2010)
Rationale and Objectives - The aim of this prospective, randomized animal study was to compare a new computer guided needle-based navigation system for liver biopsy with conventional computed tomography (CT)-guided liver biopsy. Computer-navigated interventions provide continuous needle tracking during motion and deformation from patient respiration and movement. - Materials and Methods - Twenty artificial tumors of about 5 mm in diameter were injected into the livers of five pigs, each at a different site. Each tumor was targeted by conventional CT-guided and computer navigated intervention. Intervention was considered complete after successful tumor biopsy. Data on procedure time, number of CT scans performed, accuracy, and success rate were recorded. - Results - All tumors (100%) were biopsied successfully. Mean procedural time was comparable between the two techniques (20 ± 9 minutes conventional versus 20 ± 8 minutes navigation). Mean number of CT scans were 1.2 ± 0.4 with navigation and 6.1 ± 3.8 with the conventional technique (P < .01). The dose-length product in the conventional group was significantly higher (212 ± 116 mGy × cm) than in the navigated group (78 ± 22 mGy × cm; P < .001). Mean number of capsule penetrations was 4 ± 1 with navigation versus 2 ± 1 with the conventional technique (P < .001). - Conclusion - Computer-navigated liver biopsy may provide a promising and innovative device for easy, rapid, and successful liver biopsies with low morbidity. Further technical improvements and clinical studies in humans are required.
Gesehen am 11.05.2023